Research Progress on the Formation of and Control Methods for Harmful Products from Maillard Reaction in Brown Sugar Production - LIU Jing, HAN Meiyi, HOU Liran, HU Na, YU Junzhe, XIE Caifeng (Shipin Kexue, 2023)
The Maillard reaction during the production of brown sugar is critical to the color, flavor and functional characteristics of brown sugar, but it also produces substances potentially harmful to human health such as glyoxal (GO), methylglyoxal (MGO), 3-deoxyglucosone (3-DG), 5-hydroxymethylfurfural (5-HMF), and acrylamide. This paper introduces the Maillard reaction at the key stages of the brown sugar production process, its influential factors, its possible harmful products and their effects on human health, and it puts forward some suggestions for controlling the production of harmful products from Maillard reaction during brown sugar production in order to provide a theoretical reference for improving the safety of brown sugar for consumption.